Topographical disorientation in Alzheimer's disease - Guariglia,Carla Cristina (2009)
Topographical disorientation (TD) has not been as extensively studied as other frequent manifestations of Alzheimer's disease (AD). OBJECTIVE: To verify the occurrence of TD and to identify the neuropsychological dysfunctions associated with TD in AD. METHOD: Thirty patients with probable AD, their caregivers and 30 subjects without dementia (controls) were interviewed with a questionnaire and evaluated with tests related to topographical orientation. RESULTS: AD patients, even those with mild dementia, differ from controls in the questionnaire on topographical orientation and in most neuropsychological tests except for tests of spatial working memory, point localization, three dimension and nonsense figure copy. When the performances in the neuropsychological tests of patients with mild or moderate dementia were compared, only landmark recognition and route description were more impaired in moderate dementia. CONCLUSION: TD occurs even in mild dementia of AD, a finding apparently not explained by the impairments of more elementary spatial functions.